PERSONALITY DEVELOPMENT OF EDWARD TULANE IN KATE DICAMILLO’S THE MIRACULOUS JOURNEY OF EDWARD TULANE - Sholta Aryas Rayana; Mateus Rudi Supsiadji (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
The researcher analysis Edward Tulane as the character who has experienced his personality development in his life in the novel The Miraculous Journey of Edward Tulane. The researcher formulates two research problems in this study, the objectives are to to find out of Edward Tulane’s personality and to find out Edward Tulane’s personality development in DiCamillo’s novel entitled The Miraculous Journey of Edward Tulane. The research method applied in this study is qualitative with an intrinsic approach. The study's data item is derived from the dialogue. The discussion focuses on Edward Tulane, the main character, who goes on a miraculous journey that changes his entire life. Life experience is able to change someone’s personality from a bad to a good personality. Experience and an event literally can change Edward Tulane’s life and his personality. The finding of this study is Edward Tulane's personality is changing from arrogant to a caring rabbit china doll.